IMPLEMENTATION OF NEW PUBLIC MANAGEMENT IN IMPROVING BUREAUCRACY REFORM IN THE PUBLIC SERVICES SECTOR IN GOVERNMENT AGENCIES - Firman Syah, Ardy (UIN Sunan Ampel Surabaya, 2023)
The role of the government as a public servant has been enshrined in Undang-Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara (ASN) in chapter 10, which states that ASN function as public servants. The essence of the sound of this chapter interprets the state civil apparatus as a position occupied to carry out duties and functions as a public service whose benefits can be felt directly by the community. The relationship obtained from the concept of new public management, which adopts the role of private sector services into Government Agencies with improving the quality of public services, describes a core problem that is essential to be discussed in the current era of uncertainty. This paper aims to obtain an overview of the implementation of New Public Management in all Government Agencies by considering the characteristics of each Government Agency at the Central and Regional levels to increase Bureaucratic Reforms oriented to the Public Service sector. This study uses a qualitative approach through descriptive analysis methods based on literature studies obtained and then used as material for analysis in designing the implementation of new public management in improving bureaucratic reform in the public service sector. The results of this study show that there are six aspects of implementing new public management to improve public service reform, including making service contracts, developing customer satisfaction surveys, optimizing the implementation of E-government in public service management, implementing service quality management systems, performance-based remuneration systems, and establish public-private partnerships.